Epidemiological Patterns and Clinical Consequences of Organophosphorus Poisoning - Javeria Sana Sheikh, Rida Ubaid, Shaista Alam, Pervaiz Mohammad, Mohammed Munib, Younas Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Organophosphates (OPs) are widely used chemicals with known harmful effects on human health, leading to Organophosphate poisoning (OPP). This study assesses the epidemiology and clinical outcomes of OPP in a developing country. The primary aim is to describe the characteristics and short-term outcomes of OP poisoning, including recovery and development of complications. Methods: This descriptive cross-sectional study was conducted over ten months periods at DHQ Nowshehra, involving 50 adult patients with OPP repeated over a period of 10 months. Data regarding age, gender, socioeconomic status, and hospital stay was collected. Outcomes such as coma, circulatory failure, respiratory failure, and death were monitored. Results: The study included 50 patients, predominantly young adults, with a slight male majority. Most patients recovered from poisoning effects, with a minority experiencing complications such as respiratory and circulatory failure. Mortality was recorded in 12% of cases. Conclusion: The study highlights the significant impact of OPP, particularly among young adults in rural areas. Early hospital presentation and adequate emergency care are crucial for recovery. However, the accessibility and unregulated sale of OPs pose a continued risk, especially for intentional ingestions. Keywords: Organophosphate Poisoning, Epidemiology, Clinical Outcomes, Developing Country, Emergency Care, Mortality.